UWKS Students' Perception Of The Implementation Of The Core Tax Administration System (CTAS) - Wiwin Wahyuni; Lilik Mardiana; Kharis Marpurdianto (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
To support economic transformation and encourage quality economic growth, the 2024 Draft State Budget (RAPBN) carries the theme